Development of a multivariable gene-expression signature targeting T-cell-mediated rejection in peripheral blood of kidney transplant recipients validated in cross-sectional and longitudinal samples - Christakoudi, S; Runglall, M; Mobillo, P; Tsui, T; Duff, C; Domingo-Vila, C; Kamra, Y; Delaney, F; Montero, R; Spiridou, A; Kassimatis, T; Phin-Kon, S; et al. (Elsevier, 2019)
Background Acute T-cell mediated rejection (TCMR) is usually indicated by alteration in serum-creatinine measurements when considerable transplant damage has already occurred. There is, therefore, a need for non-invasive early detection of immune signals that would precede the onset of rejection, prior to transplant damage. Methods We examined the RT-qPCR expression of 22 literature-based genes in peripheral blood samples from 248 patients in the Kidney Allograft Immune Biomarkers of Rejection Episodes (KALIBRE) study. To account for post-transplantation changes unrelated to rejection, we generated time-adjusted gene-expression residuals from linear mixed-effects models in stable patients. To select genes, we used penalised logistic regression based on 27 stable patients and 27 rejectors with biopsy-proven T-cell-mediated rejection, fulfilling strict inclusion/exclusion criteria. We validated this signature in i) an independent group of stable patients and patients with concomitant T-cell and antibody-mediated-rejection, ii) patients from an independent study, iii) cross-sectional pre-biopsy samples from non-rejectors and iv) longitudinal follow-up samples covering the first post-transplant year from rejectors, non-rejectors and stable patients. Findings A parsimonious TCMR-signature (IFNG, IP-10, ITGA4, MARCH8, RORc, SEMA7A, WDR40A) showed cross-validated area-under-ROC curve 0.84 (0.77–0.88) (median, 2.5th–97.5th centile of fifty cross-validation cycles), sensitivity 0.67 (0.59–0.74) and specificity 0.85 (0.75–0.89). The estimated probability of TCMR increased seven weeks prior to the diagnostic biopsy and decreased after treatment. Gene expression in all patients showed pronounced variability, with up to 24% of the longitudinal samples in stable patients being TCMR-signature positive. In patients with borderline changes, up to 40% of pre-biopsy samples were TCMR-signature positive. Interpretation Molecular marker alterations in blood emerge well ahead of the time of clinically overt TCMR. Monitoring a TCMR-signature in peripheral blood could unravel T-cell-related pro-inflammatory activity and hidden immunological processes. This additional information could support clinical management decisions in cases of patients with stable but poor kidney function or with inconclusive biopsy results.